Early choroidal changes detected by swept-source OCT in type 2 diabetes and their association with diabetic kidney disease. Issue 6 (23rd November 2022) - Da Silva, Monica Oliveira; Chaves, Anne Elise Cruz do Carmo; Gobbato, Glauber Correa; Lavinsky, Fabio; Schaan, Beatriz D'Agord; Lavinsky, Daniel
Abstract : Introduction: Microvascular changes in eye and kidney shares some common factors in diabetes mellitus (DM). The purpose was to evaluate choroidal thickness (CT) and choriocapillaris (CC) density in patients with type 2 diabetes (T2D) and their association with diabetic kidney disease (DKD) using swept-source optical coherence tomography (SS-OCT). Research design and methods: A cross-sectional study was conducted with patients with T2D with mild or no diabetic retinopathy (DR) and non-diabetic controls. CT was measured with SS-OCT, and CC vascular density was measured with OCT angiography. These parameters were compared with inner retinal layers thickness in patients with and without DKD and non-diabetic controls. Results: Ninety-three eyes from patients with T2D and 34 eyes from controls volunteers were included. Within the T2D group, 56 eyes with DKD and 37 eyes from patients with no diabetic kidney disease were examined. A statistically significant reduction of CT was observed in patients with DKD compared with controls, with no difference in CC density. There was an association between ganglion cell layer and central choroidal thickness reduction in the DKD group. Conclusions: Patients with T2D with DKD showed a decrease in CT with no difference in CC density compared with non-diabetic controls. This thinning might be related to vascular changes of choroidal layers such as Haller's and Sattler's with preservation of CC density, which is crucial for outer retina and retinal pigment epithelium health. Longitudinal studies are warranted to determine the association of choroidal changes with the pathogenesis of diabetes, and its association with early DKD and progression to more severe DR.